Highlights from the I international symposium of thrombosis and anticoagulation in internal medicine, October 23-25, 2008, Sao Paulo, Brazil - Lopes, Renato D.; Becker, Richard C.; Garcia, David; Hylek, Elaine M.; Granger, Christopher B.; Lourenço, Dayse M.; Nader, Helena B.; Maffei, Francisco Humberto de Abreu [UNESP]; Cesena, Fernando H.Y.; Nicolau, José C.; Timmerman, Ari; Rocha, Ana T.; et al. (Springer Nature, 2009)
The importance of thrombosis and anticoagulation in clinical practice is rooted firmly in several fundamental constructs that can be applied both broadly and globally. Awareness and the appropriate use of anticoagulant therapy remain the keys to prevention and treatment. However, to assure maximal efficacy and safety, the clinician must, according to the available evidence, choose the right drug, at the right dose, for the right patient, under the right indication, and for the right duration of time. The first International Symposium of Thrombosis and Anticoagulation in Internal Medicine was a scientific program developed by clinicians for clinicians. The primary objective of the meeting was to educate, motivate and inspire internists, cardiologists and hematologists by convening national and international visionaries, thought-leaders and dedicated clinician-scientists in Sao Paulo, Brazil. This article is a focused summary of the symposium proceedings. © Springer Science+Business Media, LLC 2009.
Keywords: Anticoagulation; Internal medicine; Thrombosis; acetylsalicylic acid; anticoagulant agent; antithrombin; antithrombocytic agent; antivitamin K; apixaban; azd 0837; betrixaban; blood clotting factor 10a inhibitor; clopidogrel; dabigatran; dalteparin; du 176b; enoxaparin; fibrinogen receptor antagonist; fondaparinux; heparin; hirulog; low molecular weight heparin; nadroparin; placebo; prasugrel; purinergic receptor blocking agent; reviparin; rivaroxaban; streptokinase; thrombin inhibitor; tm 150; unclassified drug; unindexed drug; warfarin; ym 150; acute coronary syndrome; angina pectoris; anticoagulant therapy; anticoagulation; atherogenesis; bleeding; Brazil; cerebrovascular accident; clinical education; clinical trial; deep vein thrombosis; drug mechanism; drug metabolism; embolism; endothelial dysfunction; fibrin clot; heart atrium fibrillation; heart infarction; hemostasis; heparin induced thrombocytopenia; human; internal medicine; international normalized ratio; low drug dose; malignant neoplastic disease; medical society; orthopedic surgery; oxidative stress; pharmacogenomics; practice guideline; priority journal; prosthetic valve thrombosis; recommended drug dose; risk assessment; risk benefit analysis; risk reduction; ST segment elevation; surgical risk; symposium; thrombocyte function; thrombocytopenia; thromboembolism; thrombosis; thrombosis prevention; valvular heart disease; vascular endothelium; venous thromboembolism; Anticoagulants; Congresses as Topic